The Influence Of Capital Structure, Tax Avoidance, and Profitability On The Value Of Companies In The Food and Beverage Manufacturing Subsector: Listed On The Indonesia Stock Exchange (IDX) For The Period 2015-2019 - Mahmudi, Chamdun; Bhelawati, Angelina Stela (PT Maju Malaqbi Makkarana, 2025)
This study aims to analyze the influence of capital structure, tax avoidance, and profitability on firm value in the food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period 2015-2019. Capital structure is measured using the debt to equity ratio (DER), tax avoidance is measured using the cash effective tax rate (CETR) proxy, and profitability is measured with return on assets (ROA). The value of the company as the dependent variable is measured using the price to book value (PBV). The data used is secondary data in the form of company financial statements obtained from the official IDX website. Data analysis was conducted using multiple linear regression. The research results show that capital structure has a significant impact on company value, tax avoidance does not have a significant impact on company value, and profitability has a significantly positive impact on company value.